Analisis Stimulus Respons Member Xkwavers Madura terhadap Iklan Brand Pro Israel - Zulfa Amatillah Al Qunaita; Heny Triyaningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The escalating conflict between Palestine and Israel since October 2023 has drawn global attention, including in Indonesia. This conflict has not only caused polarization among nations but has also triggered boycott movements against brands perceived as pro-Israel. One significant impact of this phenomenon is the shift in consumer attitudes, particularly within communities of Korean Wave enthusiasts, such as Xkwavers Madura. The research problem in this study is how members of Xkwavers Madura respond to advertisements from brands that are associated with being pro-Israel. This study aims to analyze the response of the Xkwavers Madura community toward advertisements from pro-Israel brands that collaborate with K-Pop idols, using a descriptive qualitative approach and the Stimulus-Response (S-R) theory. Data were collected through interviews and observations of the community’s social media activities from June to September 2024. The findings indicate a range of responses within the community, from apathy to active participation in boycott and blockout movements against brands and celebrities perceived as supporting Israel.